2005
DOI: 10.1002/ijc.20875
|View full text |Cite
|
Sign up to set email alerts
|

High ID2 protein expression correlates with a favourable prognosis in patients with primary breast cancer and reduces cellular invasiveness of breast cancer cells

Abstract: ID proteins have been implicated in the regulation of cell proliferation and differentiation in various cell types during normal development as well as in the formation of cancer. Our aim was to delineate the expression of ID2 by immunohistochemistry in primary breast cancer in order to detect potential associations with cell cycle regulatory proteins and/or clinicopathologic parameters. We further overexpressed ID2 in a breast cancer cell line to elaborate potential effects on proliferation and invasiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 27 publications
(45 reference statements)
5
45
1
Order By: Relevance
“…Several (Idb2, Tpd52, Ghr, Ppp2r) of the 32 genes identified by both approaches have previously been associated with human breast cancer (Calin et al, 2000;Gebre-Medhin et al, 2001;Boutros et al, 2004;Stighall et al, 2005), corroborating this method for identifying genes involved in early stages of mammary gland tumorigenesis. In addition, 44% of the genes identified by this approach have known roles in cellular metabolism.…”
Section: Identification Of Genes Whose Expression Changes During the supporting
confidence: 55%
“…Several (Idb2, Tpd52, Ghr, Ppp2r) of the 32 genes identified by both approaches have previously been associated with human breast cancer (Calin et al, 2000;Gebre-Medhin et al, 2001;Boutros et al, 2004;Stighall et al, 2005), corroborating this method for identifying genes involved in early stages of mammary gland tumorigenesis. In addition, 44% of the genes identified by this approach have known roles in cellular metabolism.…”
Section: Identification Of Genes Whose Expression Changes During the supporting
confidence: 55%
“…In breast cancer, Id-2 expressed at high levels maintains the cancer cells in a non-aggressive phenotype ). In addition, high level of Id-2 expression has been shown to reduce the invasiveness of breast cancer cells and can act clinically as a favourable prognostic marker (Stighall et al, 2005). Similar results have been obtained in intestinal epithelium where Id-2 promotes differentiation and inhibit tumorigenesis (Russell et al, 2004).…”
Section: Discussionmentioning
confidence: 60%
“…Id-1 has also been shown to promote metastasis through increasing invasiveness and angiogenesis in breast and prostate cancer (Fong et al, 2003;Ling et al, 2005). High level of Id-2 has been demonstrated to reduce breast cancer cells invasiveness and therefore could act as a favourable prognostic marker for breast cancer patients (Stighall et al, 2005). In addition, the methylation status of Id-4 has been shown to correlate with poor prognosis in colorectal cancer (Umetani et al, 2004).…”
mentioning
confidence: 99%
“…Recent studies have identified a nucleocytoplasmic shuffling of ID2 in vitro 48 and a favorable prognosis in breast cancer patients showing higher ID2 expression in the cytoplasm. 49 The relevance of this preliminary finding should be extended to a larger study, to further examine any relationship between ID2 localization and outcome in of late-stage ovarian cancer patients. Regardless of the role of these genes in the development of ovarian cancer, the combination of DCN and ID2 was able to significantly distinguish between participants with good or poor medium-term prognosis.…”
mentioning
confidence: 84%